Legal Responsibility For Occupational Safety Of Parcel Delivery Courier Partners In Indonesia - Alfiaturrohmania, Ulil; Fidhayanti, Dwi (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2024)
The lives of courier partners in the package delivery industry in Indonesia are full of safety-threatening challenges, especially when they use the